Integrating Various Instructional Strategies with Project Based Learning for Enhancing Knowledge and Employability in Automobile Engineering - Mistry, Roohshad; Awasekar, Dipali; Halkude, Shashikant (Journal of Engineering Education Transformations, 2017)
Interdisciplinary projects are an ideal way to prepare students of engineering in becoming professional engineers, having necessary graduate attributes (GA) in accordance with Washington Accord. These attributes have been defined for engineering graduates so that at the completion of their graduation they will be industry ready. Projects Based Learning (PBL) is the most appropriate way to prepare students for industries. The study reports the evidences of PBL for a team of 25 students for design and manufacture of a theme based automobile over a period of 10 months conducted under FSAE (Formula SAE). FSAE an interdisciplinary activity where students apply their skills for building a complex engineering product (automobile), which involves real time design, manufacture and assembly. The direct outcome of this study was student's participation in SAE Collegiate Design Series since 2012. Every year a team of 25 students participate in the PBL activity that spans over a period of 10 months. Faculty advisor integrated various instructional strategies like Think Pair Share, Peer Instruction, Out of Class Video, Flipped Classroom with the PBL for design and manufacture of an automobile. Student participants of the study not only developed thorough analytical and problem solving skills but also the necessary skills to assemble and maintain the automobile. During the entire PBL process it students were assessed for satisfactory learning at all levels of Bloom's taxonomy.Accordingly for 9GAs attainment was at high level&for 3GAs attainment was medium.